The Relationship Between Feedback Quality, Perceived Organizational Support, and Sense of Belongingness Among Conscientious Teleworkers - Liu, Yanyan; Xu, Nan; Yuan, Qinghong; Liu, Zhaoyan; Tian, Zehui (Frontiers in Psychology, 2022)
The belongingness literature has largely examined the antecedents of non-teleworkers’ sense of belongingness, but little attention has been paid to what job-related factors could affect teleworkers’ sense of belongingness. Grounded in organizational support theory, our research focuses on why feedback quality from the direct leader brings sense of belongingness and considers how conscientiousness of teleworkers shapes this effect. Based on data from 329 participants obtained at three different time points from one technology service organization in China, our results indicated that teleworkers’ perceived organizational support serves as an essential mediator of the positive relationship between feedback quality from the direct leader and sense of belongingness. Additionally, the teleworkers’ conscientiousness strengthened the positive direct effect of feedback quality on perceived organizational support and the indirect effect on sense of belongingness. The moderating role of conscientiousness in strengthening the link between feedback quality and perceived organizational support was significant for high levels of conscientiousness and not significant for low levels. Finally, we discussed theoretical and practical implications.